Hubungan Paparan Pestisida Dengan Kejadian Anemia Pada Pada Pekerja Penyemprot Pestisida Di Langkat Nusantara Kepong 2023 - Dealita Khairani Daulay (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Pesticides are toxic substances that have a negative impact on human health problems. Anemia is one of the chronic effects of pesticide. The effect of pesticides to the farmer’s health, decreasing production or increasing destruction of red blood cells. The purpose of this study was to analyze the relationship of pesticide exposure with anemia in the blood of pesticide spraying workers at PT. Langkat Nusantara Kepong Gohor Lama. The research method used is Cross Sectional at PT. Langkat Nusantara Kepong Gohor Lama with a total sample of 61 workers was obtained by Simple Random Sampling. Information was obtained through interviews with questionnaire and examination of hemoglobin levels using a portable hemoglobin meter. Based on the results of the analysis using chi square data, it was found that pesticide exposure were associated with anemia (p = 0.011). It is expected that sprayers pay more attention to the impact of using pesticides with health.